An experimental implementation of inverse finite element method for real-time shape and strain sensing of composite and sandwich structures. (15th February 2021) - Kefal, A.; Tabrizi, I.E.; Tansan, M.; Kisa, E.; Yildiz, M.
Highlights: iFEM-RZT is experimentally applied to shape sensing of a thick sandwich structure. Strain data is collected by concurrent usage of FBG sensors and strain rosettes. The results of iFEM are experimentally validated with digital image correlation. This study evidently increases the technology readiness level of iFEM methodology. Abstract: In this study, the inverse finite element method (iFEM) is experimentally applied to real-time displacement reconstruction of a moderately thick wing-shaped sandwich structure via a network of strain sensors. For this purpose, the iFEM algorithm is incorporated to the kinematic relations of refined zigzag theory (RZT) by considering laminate mechanics of the woven-fabric reinforcement. After a twill-woven wing-shaped structure is manufactured with embedded fiber Bragg grating sensors and surface mounted strain gauges/rosettes, the discrete real-time experimental strains are acquired from these sensors concurrently during a flexural test of the structure. This data is then processed by iFEM algorithm for full-field displacement and strain monitoring. Moreover, the displacement fields at the one edge of the sandwich structure is monitored by digital image correlation (DIC) system simultaneously. Furthermore, the reference displacement solutions are established by performing high-fidelity FEM analysis. Finally, the three-dimensional real-time deformations and strains obtained through iFEM approach show very good consistency when compared to the results of DIC/FEM analysis and experimental strains, respectively. Overall, the present study serves as a comprehensive experimental guidance of iFEM-based shape and strain sensing for its realistic implementation on large-scale composite structures and notably increases technology readiness level of the iFEM methodology.